Analysis of Communication Network Patterns of Home Industries (A Case Study in Tambaksari, Rowosari, Kendal) - Puteri Anidya Maulan; Danny Manongga; Irwan Sembiring (Department of Informatics, Universitas Muhammadiyah Surakarta, Indonesia, 2020)
Tambaksari is a village in Kendal Regency that has home industries (Industri Rumahan, IR). The local government classifies these industrial activities of BUMDes (Village-Owned Enterprises) into three groups, namely IR-1, IR-2, and IR-3. Each group or class has its specific criteria. The significant local potentials in Tambaksari include fish farming and processing. The advantage of the local potential in Tambaksari is inseparable from the synergy between the local government and the people of Tambaksari. This study observed the patterns of actor interactions in 64 IRs in Tambak Sari. Data were collected from questionnaires and analyzed using the Social Network Analysis (SNA) method. The results showed that Tambaksari IRs have a network density of 5.5%, which suggests that the relationship was weak. Network analysis using UCINET illustrates the separation of the IR group, which further reinforces the existence of competition in the network. The study reveals the dominant actor in the network interaction based on the measure of degree centrality, closeness centrality, and betweenness centrality. He is the actor with id # 29 who is the Chairman of IR-2, 54 years old, who has a Pindang Fish Processing.